Case Report: Fetal growth restriction and prolonged gestation associated with umbilical cord torsion and entanglement in a Holstein dairy cow - Ohsaki, Koto; Sano, Yuto; Murakami, Takashi; Ishiguro, Yuki; Ohtake, Ayaka; Sato, Ayano; Nakada, Ken; Sugiura, Tomochika (Frontiers in Veterinary Science, 2025)
This case report describes a rare instance of a bovine fetus with concurrent umbilical cord torsion and entanglement, which resulted in fetal growth restriction (FGR) and prolonged gestation. A 36-month-old primiparous Holstein cow, 285 days pregnant, was examined after failing to show signs of parturition. Fetal heartbeat was confirmed via abdominal ultrasonography until 295 days post-artificial insemination (AI) but was not detected thereafter, leading to a presumptive diagnosis of fetal death at 313 days post-AI. Following induction, the dead fetus was delivered at 316 days post-AI. Despite a gestational age of approximately 10.5 months, the fetus exhibited severe growth restriction that is equivalent to that of a normal 7-month-old fetus. The umbilical cord measured 40 cm—abnormally long for a 7-month-old fetus—and was tightly wrapped around the right hind limb with more than 360 degrees of torsion along its long axis. Maternal serum analysis revealed persistently high progesterone and markedly low estradiol concentrations before parturition, suggesting that the physiological process of parturition had not been initiated. It is speculated that the FGR resulted from chronic blood flow obstruction likely associated with the umbilical cord abnormalities, which were hypothesized to have occurred during the second trimester (approximately 4 months). The consequent absence of normal fetal signals to initiate parturition and the lack of periparturient endocrine changes contributed to prolonged gestation and underdeveloped mammary glands in the dam. This report represents the first detailed description of intrauterine umbilical cord abnormalities in cattle, demonstrating their potential to cause fetal developmental delay, prolonged gestation, and impaired mammary gland development.